Teresa: a escrita do gozo no corpo - Silva, Dayeli Francisca Ferreira da (2019)
This work was based on the autobiography of Santa Teresa De Avila, specifically its dimension of writing. She investigated how the dispersive and evanescent aspect of her own femininity gave way to a body of writing, or, in Lacan's words, a letter of joy. By using the psychoanalytical framework, we sought a theoretical tracing about writing as a metaphor of psychic inscriptions in Freud and the statute of the letter in Lacan, questioning the fact that the signifier can not answer for everything that passes in an analysis. The concept of femininity has also been taken up to think about the position of the subject in relation to the enjoyment that escapes the apprehension by the symbolic-imaginary apparatus. In retrospect, both the feminine and the writing, thought now as a letter and articulated to enjoyment, point to a surplus, so the main argument worked was that the feminine - via lalangue - could inhabit a place of enjoyment in Teresa's writing .